Komparasi Laju Pertumbuhan Miselium Jamur Tiram Putih (Pleurotus ostreatus (Jacq. ex Fr) Kummer) pada Komposisi Media Bibit (F3) dan Baglog yang Berbeda - SUDARMA, I MADE; WIJANA, GEDE; PUSPAWATI, NI MADE; SUNITI, NI WAYAN; BAGUS, I GUSTI NGURAH (Agrotrop : Journal on Agriculture Science; Vol 3 No 2 (2013))
The growth rate comparison of white oyster mushroom (Pleurotus ostreatus (Jacq. ex Fr)Kummer) mycelium in the composition of different seed (F3) and baglog media . Cultivation ofoyster mushroom (Pleurotus ostreatus (Jacq. ex Fr) Kummer) has grown rapidly along with the increasein income and health awareness. Oyster mushrooms growing need for media with a particular compositionin order to grow optimally. Oyster mushroom production is determined by the quality of the seeds (F3)is used, which is sourced from the media with good quality and composition. The research aimed todetermine the rate of growth of white oyster mushroom mycelium in the different composition of seedmedium (F3) (sawdust: fine bran: corn flour: CaCO3 ). The experiments was conducted at nurseriesand oyster mushroom development, Jl. Siulan Gang Zella No. 7 Denpasar, from June to August 2013.Each treatment contained 50 bottles, and 10 bottles only used as a sample, in environmental conditionswith temperature and humidity ranges, 20-29oC and 59-86% respectively . T-test was used todifferentiate the growth rate of white oyster mushroom mycelium with different compositions. Theresults showed that seeds (F3) derived from the growing media composition, sawdust (1 week old):fine bran: corn flour: CaCO3 (10:4:2:0,5) significantly different and better than the composition sawdust(age 1 month ): fine bran: corn flour (20:2:1:0.5), with a growth rate of mycelium in a mean 6.14±0.56cm/week and 1,81±0,82 cm/week, respectively. Spawn running in baglog with media composition10:4:2:0.5 was 2.77±1.22cm/week, but with composition media 20:2:1:0.5 mycelium could not grow.Effect of temperature and humidity on the growth rate of white oyster mushroom mycelium in seedmedia (F3) is not significantly.
Keywords: white oyster mushroom (Pleurotus ostreatus (Jacq. ex Fr) Kummer), growth rate of mycelium (spawn running), and composition of media.